2016
DOI: 10.1111/joim.12500
|View full text |Cite
|
Sign up to set email alerts
|

The formation, function and regulation of amyloids: insights from structural biology

Abstract: Amyloid diseases are characterized by the accumulation of insoluble, β-strand-rich aggregates. The underlying structural conversions are closely associated with cellular toxicity, but can also drive the formation of functional protein assemblies. In recent years, studies in the field of structural studies have revealed astonishing insights into the origins, mechanisms and implications of amyloid formation. Notably, high-resolution crystal structures of peptides in amyloid-like fibrils and prefibrillar oligomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 72 publications
2
46
0
Order By: Relevance
“…Amyloid fibrils are built from proteins that form b-strands running perpendicularly to the fibril axis [1][2][3][4][5]. Although some amyloid fibrils are functional [6][7][8][9], they are also associated with several severe diseases, including neurodegenerative disorders such as Alzheimer's disease (AD) and Parkinson's disease (PD) [1,4,10].…”
Section: Introductionmentioning
confidence: 99%
“…Amyloid fibrils are built from proteins that form b-strands running perpendicularly to the fibril axis [1][2][3][4][5]. Although some amyloid fibrils are functional [6][7][8][9], they are also associated with several severe diseases, including neurodegenerative disorders such as Alzheimer's disease (AD) and Parkinson's disease (PD) [1,4,10].…”
Section: Introductionmentioning
confidence: 99%
“…1 Known as the result of protein misfolding, amyloid fibrils are generally believed to be the major cause leading to the formation of pathogenic amyloid plaque. 2,3 On the other hand, it has been found that a variety of nonpathogenic proteins could also form amyloid fibrils with normal biological functions, indicating that formation of amyloid fibrils is a prevailing phenomenon in nature. [4][5][6] Amyloidogenic proteins or polypeptides usually came from different tissues and showed very little similarity considering their full amino acid sequences, but the amyloid fibrils they formed shared several characteristic features such as similar morphology, apple-green birefringence after Congo red (CR) staining, and specific fluorescence when binding with thioflavin-T (ThT), suggesting that there might be a common mechanism for the formation of amyloid fibrils by these different proteins or polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Following their synthesis on ribosomes as linear chains of amino acids, proteins generally must fold to unique three-dimensional structures to become functionally active. (196) Proteins are essential to cellular metabolism and communication, and they form the framework on which cells and tissues are built. To undertake these roles, most proteins fold into a specific, three-dimensional architecture that is largely determined by their distinctive sequences of amino acids.…”
Section: Mitochondrial -Lysosomal Dysfunction In Nddmentioning
confidence: 99%
“…The capacity of the chaperone system to prevent or reverse toxic aggregates declines during aging, facilitating the manifestation of a range of NDDs and other pathologies (Figures 6). (196) Amyloid diseases, or the amyloidoses, are characterized by the deposition of cross-b-sheet amyloid fibrils consisting of misfolded and/or misassembled proteins. (203)(204)(205) The amyloid fibrils that are the pathological hallmark of these disorders can be either deposited systemically or localized to specific organs.…”
Section: Mitochondrial -Lysosomal Dysfunction In Nddmentioning
confidence: 99%